Aradidae from Vietnam IV. Review of the Oriental flat bug genus Lissonotocoris Usinger & Matsuda, 1959 (Hemiptera: Heteroptera: Aradidae) - Heiss, Ernst; Bai, Xiaoshuan; Pham, Minhlan; Cai, Wanzhi (Zootaxa, 2014)
To date, only the type species Lissonotocoris membranaceus Usinger & Matsuda 1959 is known and recorded from Vietnam and China, Hainan Island. Four new species of the previously monotypic genus Lissonotocoris are described and figured: loebli n.sp. (Thailand), glabronotus n.sp. (N.Vietnam), pachycerus n.sp. (Malaysia) and siamensis n.sp. (Thailand). A key for the identification of all 5 species is provided.